PERANCANGAN SISTEM INFORMASI DATA REKAM MEDIS PASIEN RAWAT JALAN PADA KLINIK UTAMA AL-BASYARIAH CITAYAM - Noprizal Tanjung; Rachman Komarudin (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
The data of the patient's medical record greatly influence health workers in making decisions for subsequent actions taken to the patient. In managing the patient's medical record data, a medical staff of the North Sumatra Muhammadiyah Hospital will experience difficulties and require considerable time due to the data presented in the form of physical sheets that are not integrated so that report making is done manually. Recording medical record data still uses paper media. To deal with this problem can be done by developing a medical record information system at Muhammadiyah General Hospital. This application can be used in managing patient data, patient status data in, doctor's visite data, nurse's vision, prescription data, drug administration data, and patient resume data software development model using the Waterfall Model. The purpose of this study is to make medical record data safer because it is stored on the server, making medical record data easier and faster to access.